Migration and Hybrid Political Regimes Navigating the Legal Landscape in Russia - Urinboyev, Rustamjon (University of California Press, 2020)
While migration has become a vital issue worldwide, mainstream literature on migrants' legal adaptation and integration has focused on cases in Western-style democracies. We know relatively little about how migrants adapt in the ever-growing hybrid political regimes that are neither clearly democratic nor conventionally authoritarian. This book takes up the case of Russia-the third largest recipient of migrants worldwide-and investigates how Central Asian migrant workers produce new forms of informal governance and legal order. Migrants use the opportunities provided by a weak rule of law and a corrupt political system to navigate the repressive legal landscape and to negotiate, using informal channels, access to employment and other opportunities that are hard to obtain through the official legal framework of their host country. This lively ethnography presents new theoretical perspectives for studying legal incorporation of immigrants in similar political contexts. "Not only provides a brilliant analysis of the under-researched Russian case but also significantly adds to the existing knowledge of undocumentedness, informality, and migrant agency." JOAQUÍN ARANGO, COMPLUTENSE UNIVERSITY OF MADRID "Rustamjon Urinboyev's empathetic interviewing style allows him to illuminate complex social relationships, parallel legal orders, and behavioral norms. A remarkable book, rich in stories of extraordinary people, embedded in theoretical analysis." JUDITH ALLOT, UNIVERSITY OF OXFORD, RESEARCH DIRECTOR OF GULAGECHOES "Ethnographically rich and theoretically ambitious, this book reveals the extralegal negotiations through which migrant workers, employers, middlemen, and streetlevel bureaucrats negotiate the Russian migration system. An original and important contribution." MADELEINE REEVES, UNIVERSITY OF MANCHESTER